THE ROLE OF INFLATION, INTEREST RATES AND STABLE EXCHANGE RATES IS NEEDED FOR BANKING COMPANIES - Hidayatulloh, Syahrul; Marwan, Jubery; Utama, Mega Zahera (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This research aims to determine and analyze the impact of inflation, Bank Indonesia's interest rates, and exchange rates on financial performance based on return on equity in banking companies listed on the Indonesia Stock Exchange. The subjects of this research were the banking companies in Indonesia. The data source uses panel data. The sampling technique used purposive sampling with specific criteria for companies that have undergone audits and market trends that have experienced a decline, totaling twenty seven companies. Before conducting multiple regression analysis, the data underwent prerequisite tests in the form of classical assumption tests. The research results show that: With the increase in interest rates, the net asset value in the banking industry decreases. The higher the interest rate applied, the more it will reduce the amount of bank credit. The impact will reduce profits and equity. When the exchange rate of the rupiah is higher, the tendency for prices to increase affects the rise in commodity prices. Next, production costs rise, leading to a loss of product competitiveness and a decline in company performance, marked by decreasing net profit and equity.